Linking Trade and Transport Statistics: the Dutch Case - G.J.M. Linders; M.E.P. Odekerken-Smeets (European Regional Science Association (ERSA), 2006)
International trade flows are important for a trading nation such as the Netherlands. They are an important source of income, value added, and welfare. Trade flows are strongly related to transport flows of goods to and from a country. However, not all international transport flows through a country are registered as merchandize trade flows. For example, transit flows of goods are not recorded in international merchandize trade statistics. Such flows can just as well serve as a basis for value added, though. For example, goods transferred in Rotterdam harbour and transported and distributed by Dutch logistics firms create a basis for value added in services trade. Moreover, transport flows of goods entail costs as well, such as the costs of traffic congestion and environmental pollution. Therefore, it is of interest to have good information on the value and quantities of goods transported through countries, and the modes of transport used for various types of flows. For this purpose, we need integrated statistics on trade flows and transport flows in goods. To be able to match trade and transit flows with transport statistics, complete and plausible information on mode of transport and gross weight is needed. This paper describes the scope and coverage of trade statistics in comparison to transport statistics for the Netherlands. We use transport statistics to allocate the plausible mode of transport to trade and transit flows. Creating an integrated view on trade and transport flows in goods, the paper intends to contribute to an improved understanding of the impact of merchandize trade and transit flows on the economy, both in terms of domestic value added and in terms of potential social costs related to congestion and the emission of pollutants.
Keywords: 330